Comparing of the crystal structure and spectroscopic properties of some stilbazolium dyes with enlarged π-conjugated system I. Chromophores with p-dimethylamino group. (January 2017) - Bakalska, Rumyana; Todorova, Mina; Sbirkova, Hristina; Shivachev, Boris; Kolev, Tsonko
Abstract: A comparative study of the structures and spectroscopic properties of two styrylquinolinium dyes: 4-( E )-2-[4-(dimethylamino)naphthalen-1-yl]ethenyl-1-methylquinolinium iodide in an anhydrous (StructureI ), and monohydrate (StrucutureII ) forms and the newly synthesized dye 4-( E )-2-[4-(dimethylamino)naphthalen-1-yl]ethenyl-1-pentylquinolinium bromide dihydrate (III ) has been conducted by single crystal X-ray diffraction, IR- and Raman spectroscopy, UV–Vis, steady-state and time-resolved fluorescence spectroscopy, 1 H and 13 C NMR spectroscopy, and TG/DTA analyses. The structuresI, II andIII belong to a monoclinic system, space groups P 21 / c, P 21 /n, and C 2 /c, respectively. In all of the crystal structures the molecules in the asymmetric unit are in an E configuration and the naphthyl and quinolinium aromatic rings are nearly planar. The angle between the mean planes of the aromatic rings is in the range 1.43–3.65°. Calculated BLA (Bond Lengths Alternation) parameters are close to the optimal. Solvatochromism in 12 organic solvents has been investigated by using absorption and emission spectroscopy. Reversal in solvatochromic behavior of the absorption spectra has been observed. The data in solutions indicate a significant charge transfer (CT) band shifting up to 84 nm, corresponding to a great molecular first hyperpolarizability values, and very large Stokes shift up to 245 nm. The average lifetime of the fluorescence of the dyeIII, determined from the measured data by multi-order exponential decay curve fitting as 34.71 ns in benzene and 2.98 ns in DMSO. Graphical abstract: Highlights: Three crystal structures of stilbazolium dyes were compared. The influence of crystal packing factors on BLA parameter was established. The relationship between structure and photophysical properties was discussed.